Building Complexes Morphology in Traditional Pesantren of East Indonesia: A Preliminary Study - Yuli, Nensi Golda; Firmanto, Alfan; Kholis, Nurman; Sholihah, Arif Budi; Agustiananda, Putu Ayu Pramanasari; Fadlly, Harits; Akbar, Ali (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
Traditional pesantren architecture has yet to be defined by a specific building type as it encompasses both educational and residential buildings. Many researchers explore the curriculum and its educational issues, but they often overlook the fact that all activities are closely related to where they occur. The morphology of building complexes identifies the history of buildings, including the reason for their development. This paper explores the morphology of building complexes in traditional pesantren to analyze how far the development of buildings has progressed from the old traditional pesantren since its first existence in Indonesia in general and relate it to vernacular architecture around it. A pesantren in Wajo, South Sulawesi, two pesantrens in East Kalimantan, and a pesantren in Waikabubak, East Nusa Tenggara, are the case studies used to explore the morphology. The research found that all morphologies of traditional pesantren still refer to the traditional pesantren in general. However, there are some modifications because of the needs of the pesantren's capacity and the location's natural setting. Contextualizing pesantren around the community and vernacular architecture is not the main important point for the development because recently they should prioritize santris room occupancy and more accessible building construction strategies.